Informatyzacja administracyjnego postępowania egzekucyjnego i jej wpływ na skuteczność egzekucji administracyjnej .......... 303 - Nodżak, Agata (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
INFORMATISATION OF ADMINISTRATIVE ENFORCEMENT PROCEEDINGS AND ITS IMPACT ON THE EFFECTIVENESS OF ADMINISTRATIVE ENFORCEMENTThe solutions concerning the computerisation of administrative enforcement proceedings and administrative enforcement have been staggered by the Polish legislator and concern individual aspects of this procedure. When characterising the scope of computerisation of administrative enforcement proceedings, it is necessary to point out, first of all, such issues as: the transfer by the creditor to the enforcement authority of motions for the initiation of administrative enforcement, enforcement titles and information referred to in Article 26 § 1e of the Administrative Enforcement Proceedings Act, the concurrence of enforcement, the performance of seizure actions, the conduct of public auctions in electronic form or the application of certain enforcement measures. These are the areas related to the conduct of administrative enforcement proceedings in which ICT solutions unquestionably prevent the lengthiness of proceedings, accelerate their course or eliminate other hitherto existing problems related to their conduct, as a result contributing to the effectiveness of these proceedings. However, ICT solutions in themselves would prove insufficient without simultaneous substantive and procedural changes, consisting in a new shape of procedural relations between the body conducting the proceedings and its participants.